Fenomena Cerai Gugat Pada Pengadilan Agama di Malaysia dan Indonesia : Suatu Perspektif Psikologi Hukum Keluarga Islam - Mohammad Abdi Almakstur; Azni Azni; Khairil Anwar; Mardiana mardiana (Hukum Islam, 2021)
This study elaborates on the psychological causes of divorce claims made by wives against her husband in Indonesia and Malaysia. Phenomenon divorce is worth investigating because statistically, the number is much higher than the husband. The method in this research used a random sampling approach, where 400 of 200 wives from Indonesia and 200 wives from Malaysia. Sample in the research is determined randomly from various locations, namely; Religious Courts in Indonesia, Officials of the Shari'ah Court in Malaysia, Lawyers / Advocate Offices in Indonesia and Malaysia, respondents who have experienced divorce in Indonesia and Malaysia, respondents from families who are still intact in Indonesia and Malayasia, some Islamic Office in Indonesia and Official of Islamic Progress Office (JAKIM) in Malaysia. The results of this study indicate that the indicators measured from the variables indicate the existence of potential leads to divorce, indicators that are measured from the husband's behavior variable can indicate the potential to lead to divorce, the variable measuring indicator also provides guidance on the direction of divorce, then some attitude indicators bring opportunities for divorce. It is hoped that this study can be used as input for missionary activists, the head of the Office of Religion, that the occurrence of divorce from a wife statistically, the highest number divorce than a husband, is caused by psychological factors.